FINANCIAL RATIO ANALYSIS TO ASSESS PERFORMANCE FINANCE OF PAPER MANUFACTURERS ON STOCK EXCHANGE INDONESIA - Enny Istanti (JURNAL ILMIAH EDUNOMIKA, 2022)
Globalization presents a number of challenges related to human resource management.The type of research in this study uses qualitative research and is a case study.The data analysis technique used is descriptive qualitative analysis technique. The liquidity ratio can be seen by the SAIP current ratio of 155.30%, the SAIP quick ratio of 93.27%. The debt to equity ratio solvency ratio, both companies are not good, while the solvency ratio consisting of debt to total assets ratio FASW is quite good from SAIP which is 63.609%. The ratio of total asset turnover activity, financial performance of paper companies is not good because the average total asset turnover is more than 1, namely SAIP of 0.149% and FASW of 0.821%. receivable turn over FASW of 7.603%. When viewed from the comparison of profitability ratios consisting of profit margin, Return On Assets and Return On Equity FASW has the best financial performance.